Metal concentrations in the beach sediments of Bahia Solano and Nuquí along the Pacific coast of Chocó, Colombia: A baseline study (2018)
Thirty sediment samples from four different beaches along Bahia Solano and Nuquí (Department of Chocó) of eastern Colombia, with tourism and gold mining activities, were analysed to estimate the concentrations of fourteen different acid leachable metals. Metal distribution patterns showed elevated concentrations of Co, Cr, Cu, Pb and Zn compared with the upper continental crust values. Calculation of geochemical indices confirmed that the enrichment is due to periodic gold mining activities (severe to extremely severe enrichment of Cu, Zn, V, Co, Cr and Pb) along with natural (geological) contributions (minor and moderate enrichment of Ca, Mg, Fe, Ti, Mn and Li). Potential ecological risk index revealed that Pb posed the highest risk. Our results together with a global comparison suggest that the observed metal enrichments are mainly caused by mining and to a lesser extent by tourism in this region, thus instigating continuous monitoring of metal concentrations in this region. © 2018